UTILIZACIÓN DE ESTIMADORES PARA DETERMINACIÓN DE BIOMASAA CAMPO - Mónaco, N.; M. J. Rosa; V. Santa; V. Autrán; A. Heguiabehere (European Scientific Journal, ESJ, 2015)
Direct or destructive methods determine the values of existing biomass area in the field exactly. However, usually some operating and evaluation of a natural resource can be a source of disturbance to the natural system. From the contribution of new technologies, they tried to replace these methods by other direct or indirect non-destructive, where the powers of observation and estimation of biomass researchers with values obtained by cutting biomass combined. Among these methods we can name: use the double sampling rates (BEI) and estimation of direct weight field (BEP). The aim of this study was to compare the use of such estimators with sampling point scale to assess the availability of dry matter in a community located at the beginning of the origin Chucul stream. Data collection was conducted over three years (2012-2013-2014). Bimonthly, ten samples, with quadrants of 0.25 m2, spaced 30 m was cut and the biomass was weighed. 50 visual observations uncut assigning categories 1 to 5 and values estimated by the amount of forage available. Then, through linear regression, the relationship between the BEI and visually estimated BEP and cutted and weighed. The total aboveground biomass of pasture ranged from 153.52 and 386.78 g / m2. The regression estimates for different sampling dates ranged between 0.47 and 0.92 to 0.02 and 0.96 BEI and for BEP. To perform the analysis of variance estimates obtained was observed that there are significant differences between the BEI and BEP results, indicating a greater degree of adjustment for BEI to BEP. Showing that both serve as estimates of primary production in the study site.